Role of orthoptics and scoring system for orbital floor blowout fracture: surgical or conservative treatment - Timkovic, Juraj; Stransky, Jiri; Janurova, Katerina; Handlos, Petr; Stembirek, Jan (International journal of ophthalmology, 2021)
AIM: To assess the role of orthoptics in referring patients with orbital floor blowout fracture (OFBF) for conservative or surgical treatment and based on the results, to propose a scoring system for such decision making. METHODS: A retrospective analysis of 69 patients with OFBF was performed (35 treated conservatively, 34 surgically). The role of orthoptics in referring to surgery or conservative treatment was retrospectively evaluated, the factors with the highest significance for decision making were identified, and a scoring system proposed using Logistic regression. RESULTS: According to defined criteria, the treatment was unsuccessful in 2 (6%) surgically treated and only in one (3%) conservatively treated patient. The proposed scoring system includes the defect size and several values resulting from the orthoptic examination, the elevation of the eyebulb measured on Lancaster screen being the most significant. CONCLUSION: The study demonstrates the benefits of orthoptic examination when making decisions on conservative or surgical treatment and for diagnosing ocular motility disorder (with or without binocular diplopia) in OFBF patients. The proposed scoring system could, following verification in a prospective study, become a valuable adjunctive tool.
Keywords: scoring system; ocular motility; orthoptics; surgical treatment; conservative treatment; diplopia; orbital floor blowout fracture